(untitled) (Texas Journal of Medical Science, 2025)
Currently, the role of genetic factors in the development of various obesity phenotypes in individuals of different races, ethnicities, and genders is of particular interest. In particular, given the high prevalence of obesity among Uzbek women of childbearing age, studying the characteristics and genetic underpinnings of the various phenotypes of this pathology is of great importance. The action of one of the main obesity hormones, leptin, is controlled by the expression of leptin receptors, which are encoded by the LEPR gene. Mutations in this gene lead to increased leptin levels, decreased expression of the receptors that mediate its action, or altered leptin specificity, leading to the development of leptin resistance. Therefore, studying the allele and genotype frequencies of the ARG223GLN polymorphism of the LEPR gene is of great importance for the early detection and prevention of obesity in this patient population. This article examines and analyzes the prevalence of alleles and genotypes of the ARG223GLN polymorphism in the LEPR gene across various obesity phenotypes.